Performance Evaluation of IM Fed by Developed Hybrid Multilevel Inverter (DHMLI) - قريعوش جعفر; كارلو يوسف مقدسي; غسان علي حايك (Latakia University Journal -Engineering Sciences Series, 2024)
This paper presents the performance of a three-phase induction motor fed by a multilevel hybrid Inverter. This motor operates in a driving system of a port crane for small transporting containers /Electric elevator. This DHMLI provides the generation of several levels with different values to feed huge, high-power/medium loads with different medium or high voltages depending on the load to be fed. This DHMLI can be supplied from batteries, solar cells, or any other direct current source. This proposed DHMLI provides nearly sinusoidal voltages to feed the motor with a very low distortion coefficient (THD ≤ 4%), while significantly reducing the number of switches and other components. In addition, the hybrid multilevel inverter can generate high value output voltage at fixed frequency with lower switching losses, due to the high switching frequency and the proposed switch modulation (PDPWM) technique considering using (IGBT) as switches in internal design of the HMLI. Therefore, high performance and efficiency are obtained. High torque and flux control of the driven induction motor, which allows the stable operation of the crane / elevator and increase productivity when feeding the motor of the port crane from the proposed DHMLI. Achieving what are mentioned above will allow to change the value of the output voltage according to the varying of motor load and adjusting the motor speed within a specific and required range. This research paper will demonstrate the high performance, stable speed, and smooth control of the crane, since the motor is operated in a variable operating system mode within which the motor is exposed to multiple and constantly changing (starting, braking, and stopping). Performance evaluation will be achieved through the simulation of the components of the drive system independently and also for the entire system, then extracting the required curves which are analyzed in the Matlab/Simulink environment to confirm high performance characteristics and robust, considering the induction motor is the most widely used in industrial application. Index Terms: Modified hybrid multilevel inverter (MHMLI), Total harmonics distortion (THD%), Performance evaluation(PE), Phase Disposition Modulation technology(PD), Induction motor(IM).